Comparative validation of the SP6 antibody to Ki67 in breast cancer. Issue 9 (29th July 2010) - Zabaglo, Lila; Salter, Janine; Anderson, Helen; Quinn, Emma; Hills, Margaret; Detre, Simone; A'Hern, Roger; Dowsett, Mitch
Abstract : Aim: To compare SP6 and MIB1 antibodies for Ki67 staining in breast cancer. Background: Immunohistochemical detection of Ki67 has been widely used to assess the proliferative fraction in breast cancer. Ki67 is used prognostically and is the primary end-point for some presurgical trials. MIB1 has been the preferred antibody, but SP6 has become available, with apparently improved performance. The importance of Ki67 led us to systematically compare SP6 with MIB1. Methods: Two sets of tissue microarrays were used. These were constructed from formalin-fixed paraffin-embedded breast cancers: (i) 177 cancers with data on response to an aromatase inhibitor for advanced disease (cohort 1); (ii) 200 mainly oestrogen-receptor-positive cancers without response data (cohort 2). Twenty-eight pairs of core-cut biopsies taken before and after aromatase inhibitor treatment were also assessed (cohort 3). Stained sections were examined either visually or by using an image analysis system (Ariol). Results: There was a strong correlation between the two antibodies in all cohorts of samples scored visually (cohort 1: n=161, r=0.93, p<0.0001; cohort 2: n=194, r=0.84, p<0.0001; cohort 3: n=54, r=0.89, p<0.0001). Correlation between visual and Ariol scores was markedly better with the SP6 antibody (r=0.71 and r=0.88 for MIB1 and SP6, respectively). Ki67 related similarly with time-to-treatment failure with the two antibodies (cohort 1). Changes in Ki67 values with the two antibodies after 2 weeks of aromatase inhibitor treatment also correlated strongly. Conclusions: SP6 and MIB1 provide highly comparable measures of Ki67 that predict progression of advanced disease similarly. SP6 is substantially better suited than MIB1 to image analysis.